Pseudomonas brassicae sp. nov., a pathogen causing head rot of broccoli in Japan. Issue 10 (2nd October 2020) - Sawada, Hiroyuki; Fujikawa, Takashi; Horita, Harukuni
Abstract : Phytopathogenic bacteria, MAFF 212426, MAFF 212427 T, MAFF 212428 and MAFF 212429, were isolated from head rot lesions of broccoli ( Brassica oleracea L. var. italica Plenck) in Hokkaido, Japan, and subjected to polyphasic taxonomic characterization. The cells were Gram-reaction-negative, aerobic, non-spore-forming, motile with one or two polar flagella, rod-shaped and formed pale yellow colonies. Results of 16S rRNA gene sequence analysis showed that they belong to the genus Pseudomonas with the highest similarity to ' Pseudomonas qingdaonensis ' JJ3 T (99.86 %), Pseudomonas laurentiana GSL-010 T (99.22 %), Pseudomonas huaxiensis WCHPs060044 T (99.01 %), Pseudomonas japonica NBRC 103040 T (98.87 %) and Pseudomonas alkylphenolica KL28 T (98.73 %). The genomic DNA G+C content was 63.4 mol% and the major fatty acids (>5 % of the total fatty acids) were summed feature 3 (C16 : 1  ω7 c / C16 : 1  ω6 c ), C16 : 0, summed feature 8 (C18 : 1  ω7 c / C18 : 1  ω6 c ) and C17 : 0 cyclo. Multilocus sequence analysis using the partial rpoD, gyrB and rpoB gene sequences and phylogenomic analyses based on the whole genome sequences demonstrated that the strains are members of the Pseudomonas putida group, but form a monophyletic, robust clade separated from their closest relatives. Average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values corroborated their novel species status, with 88.39 % (ANI) and 35.8 % (dDDH) as the highest scores with ' P. qingdaonensis ' JJ3 T . The strains were differentiated from their closest relatives by phenotypic characteristics, pathogenicity on broccoli, and whole-cell MALDI-TOF mass spectrometry profiles. The phenotypic, chemotaxonomic and genotypic data showed that the strains represent a novel Pseudomonas species, for which the name Pseudomonas brassicae sp. nov. is proposed. The type strain is MAFF 212427 T (=ICMP 23635 T ).